2012
DOI: 10.1308/003588412x13171221589937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disinfection of flexible nasendoscopes using Tristel wipes: a prospective single blind study

Abstract: INTRODUCTIONThe otorhinolaryngology department at Northwick Park Hospital uses the Tristel wipes system for cleaning nasendoscopes in the outpatient clinics. This system uses chlorine dioxide as its only disinfectant. The manufacturer claims the system provides safe sterilisation of nasendoscopes. However, there appear to be no reports in the literature to date that evaluate the efficacy of this system in a clinical setting. The aim of this study was to evaluate the 'in use' efficacy of Tristel wipes in decont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 4 publications
1
19
1
Order By: Relevance
“…This is further supported by the absence of reports of cross-infection from flexible nasoendoscope use. Unlike some of the other recent studies [7][8][9], some of our swabs (swab 3 and 4) showed some bacterial growths following decontamination with Anioxyde 1000 and automated washer. However, none of these growths are bacterial isolates from the corresponding swab 2.…”
Section: Discussioncontrasting
confidence: 96%
“…This is further supported by the absence of reports of cross-infection from flexible nasoendoscope use. Unlike some of the other recent studies [7][8][9], some of our swabs (swab 3 and 4) showed some bacterial growths following decontamination with Anioxyde 1000 and automated washer. However, none of these growths are bacterial isolates from the corresponding swab 2.…”
Section: Discussioncontrasting
confidence: 96%
“…In our knowledge, this is the first reported study that used a nasendoscope as an in vitro test carrier in order to assess the sporicidal activity of a HLD wiping procedure. Nevertheless, a valuable study performed according to EN14561 standard (European Committee for standardization (CEN) 2007), where a frosted glass contaminated with Mycobacterium avium has undergone a disinfection with ClO 2 wipe, has already displayed a mycobactericidal activity (log 10 reduction >4) in 30 s CT with mechanical action (Tzanisakis et al, 2012). These results are consistent with those recorded in the present study despite the difference of the test carriers and the microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…13 Tzanidakis et al illustrated that tristel wipes is a viable alternative in a clinical setting for flexible nasoendoscopy decontamination. 6 Most recently Hitchcock et al showed that Tristel wipes are equal to Perasafe and Cidex OPA in terms of microbiological efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent study in the UK validated the 'in use' efficacy of tristel wipes system in 2012, a chlorine dioxide based disinfectant, in the cleaning of flexible nasoendoscopes in preventing bacterial transmission in a clinic setting. 6 The tristel wipes system is a 3-part system that kills all organisms on a pre-cleaned surface in 30 seconds. 7 It is known to be easy to use and more economic than endoscope sheaths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation